CHARACTERISTIC ANTIADJACENCY MATRIX OF GRAPH JOIN - Irawan, Wahri; Sugeng, Kiki Ariyanti (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Let be a simple, connected, and undirected graph. The graph can be represented as a matrix such as antiadjacency matrix. An antiadjacency matrix for an undirected graph with order is a matrix that has an order and symmetric so that the antiadjacency matrix has a determinant and characteristic polynomial. In this paper, we discuss the properties of antiadjacency matrix of a graph join, such as its determinant and characteristic polynomial. A graph join is obtained of a graph join operation obtained from joining two disjoint graphs and .